Pengaruh Pengelolaan Arsip Terhadap Kinerja Pegawai di Kantor Pertahanan Kabupaten Balangan - Siti Raudah; Radawiyah Radawiyah (JURNAL BISNIS DAN PEMBANGUNAN, 2023)
This study uses a quantitative approach, with causal associative research type, data collection techniques using questionnaires, observation and documentation. The population in this study were all employees of the Land Office of Balangan district 2021, totaling 38 people. The sampling technique used was Non Probability Sampling, namely Saturated Sampling or Total Sampling. Saturated sampling is a sampling technique when all members of the population are used as samples. This is often done when the population is relatively small. The results of this study indicate that the calculation of the Hypothesis Test uses a Simple Linear Regression Test and a T Test. The results of the calculation of the simple linear regression coefficient produce a value of Y = - 7.025 + 0.836 X which means that every one increase in Archive Management has an effect of 0.836 on Employee Work Efficiency, so that it can be concluded that there is an influence between variable X on variable Y. Meanwhile, from the results of the T test calculation, count is 5.674 compared to t_table (db=36) which is 2,028 with a significant level of 5%, then H1 is accepted and Ho is rejected, H1 or the Alternative Hypothesis reads " There is a positive and significant influence between Archive Management on Employee Work Efficiency in the Land Office of Balangan District". From the results of the data obtained using the SPSS 20 application, a correlation value of 0.687 is generated so that it can be concluded that the relationship between the two variables X and Y is categorized as Strong, the result of the coefficient of Determinant (r²) = 47.1% which is rounded up to 47%. The influencing factors are facilities and infrastructure factors, individual attitude factors, work procedures.To the Head of the Land Office of Balangan Regency to pay more attention to his employees, evaluate the filing system, be firm in reprimanding and giving sanctions, Regarding infrastructure so that in the future it can maximize existing infrastructure facilities, and carry out plans to increase archive space. To employees who commit violations and to the Archives Officer to pay more attention to archives in terms of managing archives so that archives are more neatly organized and do not overlap besides making it easier to search for archives if the archive is needed. Keywords: Archive Management, Employee Work Efficiency.